The Effect of Labor Force, Education, and Minimum Wage on Open Unemployment in East Java Province: A Spatial Disparity Approach 2020-2024 - PURWANDARI, Siti; HANIFA, Nurul (Journal of Tourism Economics and Policy, 2026)
Open unemployment in East Java Province shows significant spatial disparities, with urban areas like Sidoarjo (6.49) experiencing much higher rates than rural regions like Pacitan (1.56%). This study aims to examine the effect of labor force participation, education, and minimum wage on open unemployment in East Java Province for the 2020-2024 period using a spatial disparity approach. The data used are secondary from BPS and the East Java Provincial Manpower Office. The analytical method employed is panel data regression with 190 observations (38 districts/cities × 5 years), and the Fixed Effect Model was selected based on Chow and Hausman tests. The results show that minimum wage has a significant negative effect on unemployment (coefficient = -1.356300, p = 0.0003), while labor force participation (p = 0.2344) and education (p = 0.1516) show no significant effect. The model demonstrates strong explanatory power with an Adjusted R² of 81.99%. These findings indicate that minimum wage policy effectively reduces unemployment through efficiency wage effects and aggregate demand stimulation, while the insignificance of education suggests serious skills mismatch issues. The study validates Friedmann's Core- Periphery Theory, showing that structural characteristics of regions dominate unemployment dynamics over time-varying factors in East Java's heterogeneous economic landscape.